Modernity and The Islamists Notion of Active Da’wa - Ai Fatimah Nur Fuad (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2019)
This research examines the the impact of modernity that has been reshaping Muslims’ lives in Muslim societies. It particularly examines various impact of modernity such as colonialism, secularism, liberalism, and Westernisation that led Islamists to worry about the decreasing role that Islam was playing in society and in the state. Their worry about the absence of Islam in the public sphere led the Islamists to become the front line da’wa group, intensively countering the impact of modernisation in the Islamic world. This research is examined through qualitative approach combining observation and review texts. Reviewing the relevant texts and observation to the contemporary da’wa movements and individuals are conducted within both fieldwork and desk work. As the result of this research, I argue that the Islamists are the most ‘active’ Islamic da’wa movement in the modern societies including in Indonesia. Activism is their core da’wa characteristics that routinely calls on Muslims to respond to the impact of Western power. Their da’wa, therefore, is an activist ideology. This research contributes to the contemporary da’wa discourses and movements in the Muslim world.